2013
DOI: 10.1007/s11207-013-0460-z
|View full text |Cite
|
Sign up to set email alerts
|

CME Expansion as the Driver of Metric Type II Shock Emission as Revealed by Self-consistent Analysis of High-Cadence EUV Images and Radio Spectrograms

Abstract: On 13 June 2010, an eruptive event occurred near the solar limb. It included a small filament eruption and the onset of a relatively narrow coronal mass ejection ( CME ) surrounded by an extreme ultraviolet ( EUV ) wave front recorded by the Solar Dynamics Observatory's ( SDO ) Atmospheric Imaging Assembly ( AIA ) at high cadence. The ejection was accompanied by a GOES M1.0 soft X-ray flare and a Type-II radio burst; high-resolution dynamic spectra of the latter were obtained by the Appareil de Routine pour le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 49 publications
7
32
0
Order By: Relevance
“…The distance between the IL and the OL becomes larger with propagation, implying that the OL moves faster than the IL. These characteristics have been observed in other CME-driven shocks (Ontiveros & Vourlidas 2009;Chen 2011;Gopalswamy et al 2012;Eselevich & Eselevich 2012;Kouloumvakos et al 2014;Lee et al 2014), suggesting that the OL may be the front of a CME-driven shock. The double layers appear at 03:45 UT in 193Å and 211Å, and then propagate outward.…”
Section: Observationssupporting
confidence: 65%
See 1 more Smart Citation
“…The distance between the IL and the OL becomes larger with propagation, implying that the OL moves faster than the IL. These characteristics have been observed in other CME-driven shocks (Ontiveros & Vourlidas 2009;Chen 2011;Gopalswamy et al 2012;Eselevich & Eselevich 2012;Kouloumvakos et al 2014;Lee et al 2014), suggesting that the OL may be the front of a CME-driven shock. The double layers appear at 03:45 UT in 193Å and 211Å, and then propagate outward.…”
Section: Observationssupporting
confidence: 65%
“…Generally, type II radio bursts are believed to originate from the shock front, but it is difficult to determine the exact position along the shock front. Kouloumvakos et al (2014) calculated the compression ratio of the shock, and found that the type II radio burst can originate from the whole sheath region between the CME leading edge (LE) and the shock front. However, most authors considered that the source region of the type II radio burst is at a small region of the shock front (Bain et al 2012;Zimovets et al 2012;Carley et al 2013;Zucca et al 2014b;.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the type II burst kinematics were consistent with the wave and that the wave itself was consistent with a weak shock (Kozarev et al, 2011;Ma et al, 2011). The compression ratios derived from the band-split of the type II burst and from the EUV imaging data are actually consistent ( ≈ 1.5) and decline during the wave's propagation (Kouloumvakos et al, 2014). These results point to a freely propagating, shock-like disturbance.…”
Section: Metric Type II Radio Burstsmentioning
confidence: 91%
“…Several attempts have been made in the past literature to determine the density ratios X from white light (Ontiveros and Vourlidas, 2009;Mancuso, 2010, 2011) and EUV (Kozarev et al, 2011;Kouloumvakos et al, 2014;Long et al, 2015), and radio observations (Ma et al, 2011). Ontiveros and Vourlidas (2009) determined X, ranging between 1.2 and 2.8 for 11 CMEs that were faster than 1500 km s À1 observed by LASCO C2 coronagraph.…”
Section: Density Compression Ratiomentioning
confidence: 99%